HER2 Negative Mammary Paget's Disease or In Situ Melanoma? A Case Report and Review of the Literature - Luana-Andreea Boșoteanu; Mariana Așchie; Cristian Ionuţ Orǎșanu; Mădălina Boșoteanu (Hindawi Limited, 2023)
Mammary Paget's disease (MPD) is a rare histological condition, accounting for 1-4% of female breast cancers, which may appear either independently (1.4-13% of the cases), or in association with an in situ or invasive ductal carcinoma (approximately 90% of the cases). The purpose of this article is to highlight the histopathological challenges related to the microscopical polymorphism of this disease and the utmost importance of immunohistochemistry in the thorough process of Paget's disease differential diagnosis. Moreover, the primary objective of this review of literature was to corroborate the existing data concerning the potential peculiar immunohistochemical profile that mammary Paget's disease might express. We report the case of a 44-year-old female patient, histopathologically diagnosed with HER2-negative MPD accompanying an invasive mammary carcinoma. The histopathological and immunohistochemical approach is derived from the exigency of excluding the possibility of synchronous tumors-a mammary invasive carcinoma, accompanied by another component with MPD phenotypic mimicry. The unexpected negative HER2 reaction is conducted to a primary focus on excluding a malignant melanoma in situ. The absence of MelanA and S100 immunoexpression and lack of pigmentation and clinical aspects infirmed it. Bowen's disease was invalidated by its rare presentation in the breast cutaneous tissue and the absence of individual risk factors suggestive of an existing immunosuppressive status. In the case of similar morphoimmunohistochemical aspects, significant expression of Ki-67 signals MPD, an immunoreactivity that helped distinguish the cellular population from Toker cells. The great similarity of MPD with other benign and malignant cutaneous tumors might determine delay or misdiagnosis. Thus, the utmost importance of immunohistochemistry is reflected in its prognostic significance and geared towards extending the therapeutic arsenal.